Morphological characteristics and variations of the Slender racer (Orientocoluber spinalis Peters, 1866; Colubridae: Squamata) across the Republic of Korea - Il-Kook Park; Hojun Jeong; Hyerim Kwon; Jaejin Park; Jiho Park; Sang-Cheol Lee; Daesik Park (Journal of Asia-Pacific Biodiversity, 2023)
Information on the morphological characteristics of a species can assist in understanding its ecological niche and adaptation to the habitat. The Slender racer (Orientocoluber spinalis) is a near-threatened snake species in the Republic of Korea, but its morphology has not been comprehensively identified. Thus, herein, 45 O. spinalis individuals (21 females and 24 males) from four populations in the Republic of Korea were analyzed using five physical parameters and 19 scales to assess their morphological variations. Their mean snout-vent length, tail length, and body mass were 539 mm, 191 mm, and 39.5 g. Unlike previous studies, the Korean O. spinalis showed sexual dimorphism and geographic variation among populations, mainly in the relative head size. Such variations in the head size may be related to prey competition and availability. The results of this study could present indications of the adaptation of O. spinalis to each habitat that could be further verified if additional research on external environments, such as local prey sources and predators, is conducted.